The Klampid New Generation Application as a Support for the Quality of E-Government Based Public Services in the City of Surabaya - Meyva Harpy; Muchtolifah Muchtolifah; Fauzatul Laily Nisa (Department of Public Administration, 2022)
The government as a state apparatus has an important role in supporting the quality of public services. Providing services to the community is one of the functions of development with the aim of improving the welfare of the community. Community satisfaction with service quality is a benchmark for government performance in carrying out its basic functions and obligations. E-government is used in public services with the aim of providing maximum service to the community in the form of information delivery. The Surabaya City Government's efforts to improve the quality of E-government-based public services in the field of population administration are by implementing the Klampid New Generation application. This paper aims to look at the results of implementing the E-government-based Klampid New Generation application in supporting the quality of public services in the city of Surabaya. The research method in this paper uses the literature study method. To measure the application of the Klampid New Generation application in supporting the quality of public services in the city of Surabaya, using the SERVQUAL indicator as a measuring tool to what extent the implementation of E-government can fulfill service facilities in helping the community. The conclusion from this analysis is that the Klampid New Generation (KNG) program has been able to support the quality of public services in the field of population administration in the city of Surabaya.